DESIGN AND IMPLEMENTATION OF A LOW COST EXPERIMENTAL TESTBED FOR WIRELESS SENSOR NETWORKS (Nigerian Journal of Technology, 2017)
As wireless sensor networks (WSNs) become essential part of modern day infrastructure, researchers have presented loads of algorithms and models aimed at optimizing several aspects of the technology. These models are often developed and analyzed in simulated environments. The obvious need to experiment and confirm the actual performance of these algorithms and models on the field or in a more realistic environment is hampered in many cases by the high cost of advanced sensor node available in the market. This study therefore presents an inexpensive WSN test bed designed and constructed from an ESP8266EX Wi-Fi module. An experiment was conducted and results revealed that ESP8266EX based sensor nodes have a wider network coverage compared to the Arduino sensors based test bed. The proposed test bed was used to compare the performances in terms of power management of two WSN routing algorithms; normal Low Energy Adaptive Clustering Hierarchy (LEACH) and Cluster Head Assisted Routing (CHAR). Results show that the rate at which batteries depleted in LEACH and CHAR are 50% and 10% respectively; and this indicates that batteries depleted faster in LEACH than CHAR; therefore it can be stated that there is an improvement in energy conservation in CHAR over LEACH. It was also observed that CHAR produced a more even and gradual battery depletion rate leading to a longer network life of 20 rounds more than normal LEACH.http://dx.doi.org/10.4314/njt.v37i1.30